Evaluation of the health‐related quality of life in Turkish cystic fibrosis patients. Issue 8 (18th July 2021) - Alishbayli, Gulzar; Kilinc, Ayse Ayzit; Cokugras, Haluk
Abstract: Background: Prolongation of life expectancy in cystic fibrosis (CF) to the fourth decade makes health‐related quality of life (HRQOL) an important issue in this population. This study aims to evaluate the effects of clinical and socio‐demographic characteristics of patients on different aspects of HRQOL in a pediatric CF population. We also intend to assess some measures of reliability and validity of the Turkish CF Questionnaire‐Revised (CFQ‐R) forms. Methods: Fifty‐four CF patients and 46 parents / caregivers filled the appropriate CFQ‐R forms. Disease severity was evaluated via modified Shwachman–Kulczycki (SK) scores, and additional clinical information was obtained from patient records. Results: Forty‐three percent ( n  = 23) of patients were female, the mean age of patients being 13.3 ± 3.96 years. Self‐ and proxy‐reported points showed a strong correlation (Spearman's rho > 0.6) on more observable domains of HRQOL (e.g. physical functioning). No significant difference was found between sexes on any HRQOL domain. When compared between age groups, treatment burden appeared to worsen with age, while social functioning improved. All three forms of the CFQ‐R Turkish version showed acceptable internal consistency reliability and convergence with disease severity measures. Conclusions: The CFQ‐R showed a fair correlation with the Shwachman–Kulczycki score and the FEV1% value, which makes its longitudinal use possible in clinical practice. It is important to use self‐reported evaluations as well as parent / caregiver‐reported HRQOL evaluations, especially in young children. More studies are needed to assess the psychometric properties of Turkish CFQ‐R forms.